Strategi Kolaboratif Pemerintah Daerah dalam Pengembangan Destinasi Wisata Kampung Blekok di Desa Klatakan Kabupaten Situbondo - Rosadiyanto, Bagas Ubay; Ilyasi, Ach; Khotimah, Khusnul (Kolaborasi : Jurnal Administrasi Publik, 2026)
Blekok Tourist Destination in Klatakan Village, Situbondo Regency, is a themed tourism area focused on mangrove conservation and water bird preservation, serving as a major attraction that draws visitors through its natural beauty, culture, history, or human-made facilities that provide satisfaction and joy. Tourism destinations are not only evaluated by their beauty but also by the completeness of facilities, services, attractions, and ease of access. These activities encompass various functions and dimensions, including entertainment, education, culture, and economy. In line with the technological era and tourism development innovations, numerous challenges arise, such as declining visitor numbers, damaged tourism facilities, environmental degradation, and limited human resource knowledge. The objective of this research is to describe and identify the local government's strategies in developing the Kampung Blekok Tourist Destination in Klatakan Village, Situbondo Regency. This study employs a descriptive qualitative approach, utilizing primary data from in-depth interviews and secondary data. Therefore, collaborative governance strategies are essential, involving the local government, community, private sector, and local groups to achieve successful tourism destination development in Situbondo Regency, ensuring long-term growth as a primary tourism site. Effective strategies will highlight the strategic tourism potential in supporting environmental conservation while driving economic and social development in Situbondo Regency, aligning with national and regional policies for sustainable tourism sector growth.